Effect of Adding Natural Extracts on pH Value, Yield, and Organoleptic Properties of Honey Candy - Anif Mukaromah Wati; Rahayu , Premy Puspitawati; Prasetyo , Dimas Irawan; Esti , Novie Ayu Kuncoro (Journal of Agriprecision & Social Impact, 2024)
This study investigates the effects of adding various natural extracts: carrot, red ginger, mango, and tamarind on the physical and sensory properties of honey candy. Specifically, the research examines the pH value, yield, and organoleptic qualities (taste, aroma, texture, and color) of honey candy enhanced with these extracts. A laboratory experiment with a completely randomized design (CRD) was conducted, and each treatment was replicated four times. Results showed highly significant differences in the all  treatments. The highest pH was recorded with red ginger extract (5.41), while the lowest was with tamarind extract (4.02). Carrot extract yielded the highest production efficiency (61.5%), followed closely by tamarind (58%), whereas red ginger and mango showed lower yields. Organoleptic testing revealed that tamarind extract was most preferred in terms of taste and color, while mango and red ginger improved texture. Red ginger, however, received lower scores for taste and aroma, likely due to its strong spicy profile. Overall, the addition of natural extracts significantly impacted the quality of honey candy, with tamarind and carrot extracts demonstrating the most favorable effects on yield and sensory attributes, making them promising choices for enhancing functional candy products.